An updated checklist of the ground beetles (Coleoptera: Carabidae) of Sardinia - Taglianti, Augusto Vigna (Zootaxa, 2009)
An up-to-date checklist of the ground beetles of Sardinia and surrounding islets is presented. The presence on the island of 379 species is confirmed, while 41 are here considered of doubtful occurrence. All endemic elements are indicated and concise information is given on the Italian distribution of each species, together with the chorotype of recurrent pattern of main distribution.